CD4 Count at Entry into Care and at Antiretroviral Therapy Prescription among Adults with Human Immunodeficiency Virus in the United States, 2005-2018. (31st December 2020) - Lee, Jennifer S; Humes, Elizabeth A; Hogan, Brenna C; Buchacz, Kate; Eron, Joseph J; Gill, M John; Sterling, Timothy R; Rebeiro, Peter F; Lima, Viviane Dias; Mayor, Angel; Silverberg, Michael J; Horberg, Michael A; et al.
Abstract: From 2005 to 2018, among 32013 adults with human immunodeficiency virus entering care, median time to antiretroviral therapy (ART) prescription declined from 69 to 6 days, CD4 count at entry into care increased from 300 to 362 cells/μL, and CD4 count at ART prescription increased from 160 to 364 cells/μL.